2018
DOI: 10.1186/s12966-018-0752-7
|View full text |Cite
|
Sign up to set email alerts
|

Association between breakfast composition and abdominal obesity in the Swiss adult population eating breakfast regularly

Abstract: BackgroundEvidence from experimental and observational studies is limited regarding the most favorable breakfast composition to prevent abdominal fat accumulation. We explored the association between breakfast composition (a posteriori derived dietary patterns) and abdominal obesity among regular breakfast eaters from a Swiss population-based sample.MethodsThe cross-sectional survey assessed diet using two 24-h dietary recalls in a nationally representative sample of adults aged 18 to 75 years. We derived diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
2
14
2
1
Order By: Relevance
“…Some other studies, such as those of Rezazadeh and Rashidkhani 41 and Shin et al 45 showed that healthy dietary patterns were inversely related to the risk of overweight or obesity. However, the "prudent" dietary pattern identified in the study of Chatelan et al, 9 which is similar to the dietary pattern of "fruits, vegetables, and eggs" in our study, had an inverse relationship with central obesity, inconsistent with our findings. This may be due to different factor loadings in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Some other studies, such as those of Rezazadeh and Rashidkhani 41 and Shin et al 45 showed that healthy dietary patterns were inversely related to the risk of overweight or obesity. However, the "prudent" dietary pattern identified in the study of Chatelan et al, 9 which is similar to the dietary pattern of "fruits, vegetables, and eggs" in our study, had an inverse relationship with central obesity, inconsistent with our findings. This may be due to different factor loadings in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the dietary pattern of "sweets, tea and coffee" in our study is similar to the traditional dietary pattern reported by Chatelan et al 9 of white bread, butter, and sweet spread, and the third dietary pattern identified by Iqbal et al 40 (high factor load for sugar and confectionary, eggs, butter, and bread). Furthermore, the dietary pattern of "fruits, vegetables, and eggs" in our study is similar to the second dietary pattern ("prudent"-fruit, unprocessed and unsweetened cereal flakes, nuts/seeds, yogurt) in the study of Chatelan et al 9 as well as the Northern Brazil dietary pattern reported by Baltar et al 38 (positive factor loadings for meats, preparations with corn, eggs, tubers/roots/potatoes, dairy products, savory snacks/crackers, fruit juices/fruit drinks/soy-based drinks).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This variability may be primarily attributed to lifestyle difference throughout China. Studies have shown that a variety of lifestyle factors can influence the incidence of central obesity, such as breakfast composition and sleep duration (29,30). School education related to diet and lifestyle can reduce the incidence of central obesity in pre-teenagers, despite a tendency in this group toward decreased physical activity and increased screen time (31).…”
Section: Discussionmentioning
confidence: 99%
“…Despite many studies reporting the importance of breakfast [61,62], perhaps not everyone (especially late chronotype) can benefit from its advantages. The composition of meals can also affect or alter the beneficial effects of breakfast [63,64]. Thus, the current review suggests the needs for further research to establish appropriate meal timing and composition that are personalised to an individual's circadian clock.…”
Section: Dietary Behaviourmentioning
confidence: 99%